Correction: Factors associated with suicide/self-inflicted injuries among women aged 18-65 years in the United States: A 13-year retrospective analysis of the National Inpatient Sample database. - Oluwasegun Akinyemi; Temitope Ogundare; Adeolu Funso Oladunjoye; Kindha Elleissy Nasef; Christina Lipscombe; John Akinshola Akinbote; Maureen Bezold (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0287141.].